RUH ISLAM DALAM âWADAGâ LOKAL MADURA: Kasus âTanean Lanjengâ - Susanto, Edi (JURNAL KARSA (Terakreditasi No. 80/DIKTI/Kep/2012), 2012)
AbstracThis paper presents an interaction between Islam and local culture of Madurese. The locus of the study has been Taneyan Lanjeng. It is viewed as a total reflection of Madurese in applying the thought of Islam, thus it is well-off Islamic values. The digging of meaning behind Taneyan Lanjeng, as cultural metaphor, is necessaity to realize Islam as an environment-care religion. The term of environment covers social, cultural and perhaps natural environments Kata-kata kunciruh Islam. tanèyan lanjèng